Hearing Recovery Induced by DNA Demethylation in a Chemically Deafened Adult Mouse Model - Deng, Xin; Hu, Zhengqing (Frontiers in Cellular Neuroscience, 2022)
Functional hair cell regeneration in the adult mammalian inner ear remains challenging. This study aimed to study the function of new hair cells induced by a DNA demethylating agent 5-azacytidine. Adult mice were deafened chemically, followed by injection of 5-azacytidine or vehicle into the inner ear. Functionality of regenerated hair cells was evaluated by expression of hair cell proteins, auditory brainstem response (ABR), and distortion-product otoacoustic emission (DPOAE) tests for 6 weeks. In the vehicle-treated group, no cells expressed the hair cell-specific protein myosin VIIa in the cochlea, whereas numerous myosin VIIa-expressing cells were found in the 5-azacytidine-treated cochlea, suggesting the regeneration of auditory hair cells. Moreover, regenerated hair cells were co-labeled with functional proteins espin and prestin. Expression of ribbon synapse proteins suggested synapse formation between new hair cells and neurons. In hearing tests, progressive improvements in ABR [5–30 dB sound pressure level (SPL)] and DPOAE (5–20 dB) thresholds were observed in 5-azacytidine-treated mice. In vehicle-treated mice, there were <5 dB threshold changes in hearing tests. This study demonstrated the ability of 5-azacytidine to promote the functional regeneration of auditory hair cells in a mature mouse model via DNA demethylation, which may provide insights into hearing regeneration using an epigenetic approach.